STRATEGI GURU DALAM MENINGKATKAN LITERASI NUMERASI SISWA SEBAGAI UPAYA MEMPERSIAPKAN TES KEMAMPUAN AKADEMIK (TKA) - Ardani, Anwar; Amantiya Putri, Cindy; Sholihah, Nur Itsna; Inayah, Uti Khusna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Numeracy literacy is one of the essential competencies that students need to develop in preparation for the Academic Competency Test (Tes Kemampuan Akademik/TKA). However, students' numeracy literacy skills remain a challenge in elementary education, requiring teachers to implement effective learning strategies. This study aimed to describe teachers' strategies for improving students' numeracy literacy in preparation for the Academic Competency Test at MI Modern Satu Atap Al-Azhary. This research employed a qualitative descriptive approach. The research participants consisted of the principal, sixth-grade teachers, and sixth-grade students selected through purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings revealed that teachers implemented various strategies, including habituation to solving mathematical word problems, a 15-minute reading activity before lessons, the utilization of literacy corners, differentiated practice exercises, peer tutoring, ability-based learning groups, after-school tutoring programs, and collaboration with parents. These strategies contributed to strengthening students' numeracy literacy and improving their readiness for the Academic Competency Test. The study concludes that systematic and continuous implementation of these strategies can support the development of students' numeracy literacy and may serve as a reference for elementary schools in preparing students for the Academic Competency Test.